Mobiles reinventing shopping: A critical review - Dulloo, Rhytheema (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to provide clear understanding of the increasing use of mobiles for shopping to e-tailers by classifying and organizing an exhaustive review of prior theoretical literature. To conduct the review author draws a sample of 250 articles published from addressing mobile shopping behavior of customers. This paper provides foremost organized review of mobile shopping literature thus providing opportunities for brands to build a focused marketing tactic to enhance mobile shopper engagement, leading to increased sales.Â Â